2001
DOI: 10.1097/00007632-200103150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Load-Sharing Between Anterior and Posterior Elements in a Lumbar Motion Segment Implanted With an Artificial Disc

Abstract: The models suggest that, by altering placement of the artificial disc in the anteroposterior direction, a surgeon can modulate motion-segment flexuralstiffness and posterior load-sharing, even though the specific disc replacement design has no inherent rotational stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(136 citation statements)
references
References 33 publications
6
127
0
3
Order By: Relevance
“…A variety of studies have carefully analyzed the biomechanical properties and motion characteristics of different artificial disc-design prosthesis [12,13,16,17,22,24,25,36,47,50,53,54]. Reported problems associated with TDR include excessive ligament torsions, increased facet pressures, a high risk of instability at the index and adjacent level, up to 2.59 increased load on posterior structures and altered load patterns with sudden rather than gradual load increase in the facet joints [17,39].…”
Section: Biomechanical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have carefully analyzed the biomechanical properties and motion characteristics of different artificial disc-design prosthesis [12,13,16,17,22,24,25,36,47,50,53,54]. Reported problems associated with TDR include excessive ligament torsions, increased facet pressures, a high risk of instability at the index and adjacent level, up to 2.59 increased load on posterior structures and altered load patterns with sudden rather than gradual load increase in the facet joints [17,39].…”
Section: Biomechanical Studiesmentioning
confidence: 99%
“…Reported problems associated with TDR include excessive ligament torsions, increased facet pressures, a high risk of instability at the index and adjacent level, up to 2.59 increased load on posterior structures and altered load patterns with sudden rather than gradual load increase in the facet joints [17,39]. Furthermore, it has been shown that TDR with Charité III did not restore the physiological segmental rotational stability with additive destabilising effects for multilevel versus monosegmental TDRs [13,47].…”
Section: Biomechanical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several finite-element studies, which have already addressed similar problems and which came to the conclusion that an anterior centre of rotation, in case of semi-constrained prosthesis, would result in a decrease of the flexion ability [7,21,23,29]. The limited value of this study is based on the fact that only the flexion ability (and not flexion/extension) was analysed and that the difference between the centre of rotation (anterior vs. posterior) averaged 8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Although some TDRs are in use for several years and are clinically established, such as the Charité-Prosthesis with its unconstrained and the Prodisc-Prosthesis with its semi-constrained disc kinematic, little is known about the impact of different disc kinematics on biomechanical behaviour of the lumbar spinal unit. Also the variable centre of rotation in case of semi-constrained prosthesis is supposed to be of crucial importance for segmental biomechanics [2,7]. Further insight into the biomechanical behaviour of TDR could help to assess clinical outcome better.…”
Section: Introductionmentioning
confidence: 99%